2019
DOI: 10.1090/ecgd/335
|View full text |Cite
|
Sign up to set email alerts
|

Almost Kenmotsu metric as a conformal Ricci soliton

Abstract: The object of the present paper is to characterize two classes of almost Kenmotsu manifolds admitting Ricci-Yamabe soliton. It is shown that a (k, µ) ′ -almost Kenmotsu manifold admitting a Ricci-Yamabe soliton or gradient Ricci-Yamabe soliton is locally isometric to the Riemannian product H n+1 (−4) × R n . For the later case, the potential vector field is pointwise collinear with the Reeb vector field. Also, a (k, µ)-almost Kenmotsu manifold admitting certain Ricci-Yamabe soliton with the curvature property … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In [4], Dileo and Pastore presented an example of a (2n + 1)-dimensional (k, µ) ′almost Kenmotsu manifold. In [3], the authors studied this for 5-dimensional case and obtained k = −2. We now mention the necessary results from that example to verify our result.…”
Section: Example Of a Shrinking Quasi Yamabe Solitonmentioning
confidence: 99%
“…In [4], Dileo and Pastore presented an example of a (2n + 1)-dimensional (k, µ) ′almost Kenmotsu manifold. In [3], the authors studied this for 5-dimensional case and obtained k = −2. We now mention the necessary results from that example to verify our result.…”
Section: Example Of a Shrinking Quasi Yamabe Solitonmentioning
confidence: 99%
“…in [10] showed that if a Lorentzian α-Sasakian manifold admits conformal Ricci soliton and is Weyl conformally semi-symmetric, then the manifold is η-Einstein. Again in [9] it has been proved that a (k, µ)…”
Section: Introductionmentioning
confidence: 98%
“…Dey et.al. [8] studied conformal Ricci solitons on almost Kenmotsu manifolds. Siddiqui [22] studied conformal Ricci solitons of Lagrangian submanifolds in Kahler manifolds.…”
Section: Introductionmentioning
confidence: 99%